2021
DOI: 10.3390/pharmaceutics13111967
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Chimeric HPV-HIV Protein L1P18 in Pichia pastoris; Purification and Characterization of the Virus-like Particles

Abstract: Currently, three human papillomavirus (HPV) vaccines are already licensed and all of them are based on virus-like particles (VLPs) of HPV L1 capsid protein but not worldwide accessible. While about 38.0 million people were living with HIV in 2019, only 68% of HIV-infected individuals were accessing antiretroviral therapy as of the end of June 2020 and there is no HIV vaccine yet. Therefore, safe, effective, and affordable vaccines against those two viruses are immediately needed. Both HPV and HIV are sexually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…It could be attributed to the negative stain reagent that we used in this study. In our recent study published in previous study [ 37 ] and another ongoing paper under peer review (data not shown), we have got good quality and resolution of electron micrographs when yeast- and baculovirus-derived L1:P18I10 VLPs (the same chimeric construct) were equilibrated in PBS and negative-stained with phosphotungstic acid (PTA). Because we used the different VLP production and purification system in this study, mammalian cell-derived L1:P18I10 and L1:T20 VLPs were equilibrated with Tris-HCl and negative-stained with uranyl acetate.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It could be attributed to the negative stain reagent that we used in this study. In our recent study published in previous study [ 37 ] and another ongoing paper under peer review (data not shown), we have got good quality and resolution of electron micrographs when yeast- and baculovirus-derived L1:P18I10 VLPs (the same chimeric construct) were equilibrated in PBS and negative-stained with phosphotungstic acid (PTA). Because we used the different VLP production and purification system in this study, mammalian cell-derived L1:P18I10 and L1:T20 VLPs were equilibrated with Tris-HCl and negative-stained with uranyl acetate.…”
Section: Resultsmentioning
confidence: 93%
“…The HPV:HIV (L1:P18I10 and L1:T20) VLP samples were serially purified using cation exchange (Capto SP ImpRes, GE, Boston, MA, USA), size exclusion (Capto Core 700, GE) and affinity (HiTrap Heparin HP, GE) chromatography. The chromatographic protocols were described in our previous studies [ 36 , 37 ] and following the manufacturer’s protocol [ 38 ]. The L1 protein signal in each purification step was characterized by Western blot analysis and probed with anti-HPV16 L1 antibody CAMVIR-1 [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…This clinical trial has achieved partial protection, inducing a low protective efficacy of 31.2% against HIV-1 infection in Thailand [89,92]. The P18I10 peptide (RGPGRAFVTI) form the V3 loop of HIV-1 gp120 is inserted to the D-E loop of the HPV L1 capsid, the resulting chimeric VLPs vaccine named L1P18 is expressed in yeast aiming to elicit protective effect against both HPV and HIV [93]. Further efficiency test of this construct will be conducted in future study.…”
Section: Hiv-1 Vaccinementioning
confidence: 99%
“…The intracellularly expressed chimeric L1P18 protein was purified via size exclusion chromatography, ultracentrifugation, and ultrafiltration with 96% purity and a recovery yield of 9.23%. The approach highlights bivalent vaccines’ easy and reliable production against major global pathogens using an alternative yeast-based expression platform [ 95 ]. In another study, researchers developed a multi-component malarial vaccine consisting of distinct parasite ligands of Plasmodium falciparum , namely, PfAMA-1 (domain III of apical membrane ag-1), PfMSP1 (merozoite surface protein), and PfEBA-175 (binding domain for glycophorin A on erythrocytes).…”
Section: Expression Platforms and Upstream Process Development Of Chi...mentioning
confidence: 99%